REFLECTION OF LONELINESS IN THE ACADEMIC LIFE OF UNIVERSITY STUDENTS - Clara Lima Moreira, Ana; Gabriele Silva Andrade, Yohana; Andrade Barbosa, Henrique; Myllene Durães Leite, Sâmmyla; Gomes Versiani, Lamonielly; Gonçalves Silva, Dinariam; Silva Borges, Jhulie; Antunes Aquino Cardoso Gonçalves, Sueli; Luiz de Moura, Walter; Siega Nepomuceno, Matheus; Gonçalves Souto, Rhaissa; Soares da Silva, Leniane; et al. (Health and Society, 2026)
Introduction: Loneliness transcends the mere absence of social interaction, manifesting itself even in contexts of coexistence, especially when the relationships established lack depth or satisfaction in the university environment, this reality becomes particularly evident. Objective: to identify the levels of loneliness among university students. Materials and methods: This is a descriptive study, with a quantitative approach, aimed at the objective analysis of the collected data. The information was collected through a questionnaire, generating numerical data. The study was conducted at the FASI/FUNORTE university center. The target audience was students of the courses offered by these institutions, totaling 3,780. Of this total, 265 were randomly selected academics. The FASI and FUNORTE faculties authorized the collection of data through the signing of the TCI and the participants were informed about the goals and guarantees of confidentiality, giving their consent through the TCLE. Conclusion: It was possible to affirm that the objective was fully achieved in view of the data obtained during the research and proven by the number of 99.6% of university students who feel alone, an alarming and worrying number.